Pengaruh Corporate Social Responsibility (CSR) dan Intellectual Capital terhadap Kinerja Keuangan - Linda Dwi Vebriyani,; Sri Suartini; Hari Sulistyo (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to examine the social problem is a complex problem, because it is related to the interests of various parties who are interconnected with the company, namely analyzing and explaining the description of the variables and the influence of Corporate Social Responsibility (CSR) and Intellectual Capital on Financial Performance. The research method used in this research is regression research with a quantitative approach. The population used in this study are all banking companies listed on the Indonesia Stock Exchange from 2015 - 2020. This study has a total population of 42 companies. The sample selection method used in this research is the Purposive Sampling Method, so 15 samples of banking companies are obtained which will be used as data sources for analysis. The results of the analysis show that CSR has an effect on Financial Performance (ROA) so that the higher Corporate Social Responsibility (CSR) it will affect the Financial Performance (ROA) of the banking company. Likewise, IC has an effect on Financial Performance (ROA), which means that IC partially has a positive and significant effect on Financial Performance (ROA). This means that the greater the IC, the higher the Financial Performance (ROA) in banking companies. On the simultaneous influence of CSR and IC simultaneously have a positive and significant effect on the Financial Performance (ROA) of banking companies in the research period Keywords: CSR, IC, ROA